Analysis of selected bioactive compounds and biological activities of untreated, germinated and fermented mung bean aqueous extracts - Mohd Ali, Norlaily (2013)
Mung bean (Vigna radiata), a legume plant with seed that is frequently consumed in Asia is gaining its popularity worldwide. Germination and fermentation processes are well documented to increase the concentration of various bioactive compounds as well as to enhance the organoleptic characteristics and nutritional values of various foods. The use of common treatments such as chemotherapy drugs, radiotherapy and surgery to treat various diseases have been reported to cause adverse side effects, induce drugs resistancy, which reduced their effectiveness and initiation of other diseases. Therefore, alternative therapy using natural active compounds from mung bean plant was employed. Although mung bean plant has been consumed traditionally, very limited scientific reviews have been reported regarding its benefits and efficacy. The purpose of this study was to examine the bioactive compounds and biological activities of mung bean (MB), germinated mung bean (GMB) and fermented mung bean (FMB) aqueous extracts. More specifically, the content of amino acids, y-aminobutyric acid (GABA) and total phenolic compound (TPC) were evaluated along with their effects as immumodulator, cytotoxic, hepatoprotectant, anti-inflammatory and anti-nociceptive. Results showed that the content of total free amino acid and essential amino acids increased by 12-fold and 17-fold in GMB and 13-fold and 26-fold in FMB. On contrary, only fermentation was able to accumulate TPC with increment by 4-fold compared to untreated mung bean. To demonstrate the multiple biological properties of extracts, various Reactive Oxygen Species (ROS)-related diseases were employed throughout the study for instance immune system dysfunction, cancer, alcoholic liver disease (ALD), inflammatory and pain-related inflammatory. In immunomodulatory study, immune cells (mice splenocytes) treated with FMB aqueous extract resulted in stimulation of cell proliferation and cytokines expression. Cytotoxicity study revealed that FMB was selective against breast cancer cells (MCF-7) with IC50 2.3 mg/mL and decreased cell viability by 50% after 72 h of incubation. Meanwhile, increased detection of phosphatidylserine (PS) and Sub-Gs/G, cells population with Sub-Gs/G, population increased significantly from 1.08 ± 0.06% to 21.5 ± 0.23% indicating the increase of cancer cell death via apoptosis. Hepatoprotective effect of GMB and FMB on alcoholinduced liver injury in mice was found to be higher than MB where the elevated level of liver function biomarkers (alanine aminotransferase (ALT), aspartate aminotransferase (AST), cholesterol, triglycerides (TG)) and antioxidant liver homogenate (Malondialdehyde (MDA), superoxide dismutase (SOD), Ferric Reducing Antioxidant Power (FRAP» reverted close to normal. Treatment with FMB at high dose (1000 mg/kg) displayed the highest suppression percentage of all serum markers, 63.73% (ALT), 69.84% (AST) 38.4% (TG) and 23.42% (cholesterol). Also, FMB was able to reduce the level of MDA by 3.6 fold, nitric oxide (NO) by 1.6 fold, SOD by 2.3 fold and FRAP activity by 2.2 fold. Similarly, histopathological evaluation of extracts particularly GMB and FMB on alcohol treated liver tissues resulted in the reduction of sinusoidal and central vein dilations, ballooning and hepatocytes necrosis. In antiinflammation and anti-nociceptive study, all extracts showed no sign of toxicity on normal murine macrophages (RAW 264.7) cells meanwhile, merely GMB and FMB were able to inhibit the stimulation of pro-inflammatory mediator NO. Study on mice showed that both GMB and FMB exerted significant anti-inflammatory effect with earoedema inhibition by 18% and 35% respectively. Apart from that, in heat-induced central pain study, all extracts at certain interval time showed anti-nociceptive effect against pain stimulus. Germination and fermentation successfully enhanced the nutritional values of mung bean in term of bioactive compounds and biological properties. These findings indicated the novel approach of anaerobic germination and fermentation using Rhizopus sp. 5351 on mung bean and the potential of FMB and GMB extracts to improve the clinical symptoms of immune, cancer, liver and inflammation associated diseases.